Atopic dermatitis among children and adolescents in the Arctic region – a systematic review and meta‐analysis. (16th May 2021) - Andersson, A.M.; Halling, A.S.; Loft, N.; Skov, L.; Koch, A.; Guttman‐Yassky, E.; Thyssen, J.P.
Abstract: The prevalence of atopic dermatitis (AD) varies across the globe, and the clinical phenotype with racial background and ethnicity. AD in the Arctic region has only been scarcely studied. We performed a systematic review and meta‐analysis to examine the prevalence, clinical manifestations and risk factors for AD among children and adolescents in the Arctic. Three medical databases PubMed, Embase and Web of Science were screened. All studies published between 1990 to 2020 with epidemiologic data on AD in children and adolescents in the Arctic region, were included. Data were extracted and a meta‐analysis was performed to obtain pooled proportions and incidences with 95% confidence intervals (CI). We identified 21 studies from 8 different Arctic regions with 31 403 participants. The cumulative incidence of AD was 23% (95% CI 20–26) and 1‐year prevalence was 19% (95% CI 15–25). The incidence of AD was higher in the Arctic parts of Scandinavia and lower in Greenland and Russia. Children of indigenous descent had a slightly lower incidence of AD (19%, 95% CI 13–26) compared to the overall population. The dominant phenotype of AD was mild to moderate flexural dermatitis with facial involvement. Asthma and allergic rhinitis were common and observed in 20–30% of children with AD. In conclusion, AD is highly prevalent in the Arctic, but varies between regions and races. Indigenous children living in less urbanized countries appear to have a slightly lower risk of AD. Future studies should confirm this and examine whether this correlation relates to behavioural differences or genetic signature.